Saint Joaquim's Fort: from the milestone of the portuguese occupation on the Rio Branco valley to the battles of memory - XVIII to XX centuries - Vieira, Jaci Guilherme; Filho, Gregorio Ferreira Gomes (Textos e Debates, 2016)
This article talks about the role of Saint Joaquim’s Fort in the consolidation of the border and of the occupation of the Rio Branco valley, located in the current State of Roraima. It strives to comprehend the process of occupation of the region in the end of the XVIII and XIX centuries, describe the colonial policies of the Portuguese and the Brazilian Empire alike, to discuss questions related to the memory of Saint Joaquim’s Fort, trying to emphasize the subjects who participated in this process. Moreover, there is a discussion about the dispute over Saint Joaquim’s Fort, a question that involves several segments of Roraima’s society, a memory that was appropriated by the so called “pioneer” families because some of them had their origins bound to ex-participants of the fortification and utilized them to justify their possessions and to consolidate their social place.